Sohibul Hikayat: Text, Context, and Defense - Rohim; Purwaningsih; Dea Letriana Cesaria; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2022)
Sohibul Hikayat is a traditional art of speech performance presented by storytellers from the Betawi region who came from the Middle East. Therefore, the stories told in Sohibul Hikayat, among others, came from Persia, such as One Thousand and One Nights, Nurul Laila, and Alfu Lail wal Lail. The storyteller is presented in the form of prose, and even some rhymes are inserted, there are no specific scenes or humorous characters, such as in wayang, mask, or lenong. The purpose of writing this article is to find out the text, context, and survival of Sohibul Hikayat's oral tradition in the community by making efforts to protect Sohibul Hikayat's wealth as a national asset from extinction, documenting Sohibul Hikayat as an effort to preserve, study in the form of analysis and grouping Sohibul Hikayat status. The stories in Sohibul Hikayat often combine fictitious stories and true stories. The combination of these two types of stories aims to educate and convey the moral message to the listeners. Interesting stories accompanied by interludes of humor in it are also a special entertainment for connoisseurs Sohibul Hikayat. The story of Sohibul Hikayat has many values that can be drawn from the moral meaning and entertainment, this oral literature should be introduced back into society.